Navigating the Terrain of Entrepreneurship Education in Neoliberal Societies - Karin Berglund; Ulla Hytti; Karen Verduijn (Sage, 2022)
This article offers reflections based on the special issue on unsettling entrepreneurship education (EEP 3(3)) in which contributions have resisted the tendency to see students as consumers with the ‘right’ to take part in entrepreneurship education (EE) so as to effectively shape their enterprising selves. Here we resume our editorial discussions of what unsettling entrepreneurship education could mean for us – as entrepreneurship researchers and as teachers – and seek to mark out new directions both for research and education by reflecting upon ethical perspectives, identity work, and how EE can be seen to create an affective and emotional workspace. These aspects not only invite us to ask new research questions, but may also challenge our position as teachers in EE and invite us to reflect upon our view of students. To frame the need of continuous reflection, when navigating the terrain of EE in neoliberal society, we both take off and arrive in the current Covid-19 pandemic and suggest that this crisis can teach us something as valuable as ‘standing still’, which helps us all to reconsider what kind of entrepreneurial society that we build together with our students in entrepreneurship education.